Pengaruh Penerapan Metode One Day One Ayat Terhadap Keberhasilan Hafalan Al-Qur’an Juz 30 (Penelitian di Kelas VIII Mts Al - Musaddadiyah Garut) - Fauziah, Hapsah; Zakiah, Rifa Atul (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
The process of memorizing the Qur'an is widely practiced in both formal and non-formal educational settings. The "One Day One Ayah" (ODOA) memorization model is an effective and rapid method for memorizing the Qur'an, as it is highly practical in its application. This method facilitates teachers in training and teaching memorization and makes it easier for students to memorize. The ODOA method has been implemented successfully in various institutions, such as Rumah Tahfidz Al-Ikhlash Karangrejo Tulunggagung and TK Masyithoh Al Iman Bandung Jetis Pendowoharjo Sewon Bantul, proving its effectiveness in enhancing Qur'anic memorization. One of the formal schools adopting this memorization process is Mts Al-Musadaddiyah Garut. The memorization process naturally involves methods that support successful Qur'an memorization. The ODOA method introduces a novel approach to memorization with a program focusing on memorizing one verse per day, starting from the shorter chapters (Juz 30). This study aims to: (1) explore the implementation of the ODOA method at Mts Al-Musadaddiyah Garut; (2) assess the success in memorizing Juz 30 of the Qur'an among eighth-grade students at Mts Al-Musadaddiyah Garut; and (3) determine the impact of the ODOA method on the success of memorizing Juz 30 among eighth-grade students at Mts Al-Musadaddiyah Garut. This investigation seeks to understand the relationship between the implementation of the ODOA method in Qur'anic memorization classes (Variable X) and the success in Qur'anic memorization among students (Variable Y). This research employs a descriptive quantitative approach, using data or information concerning the studied phenomenon. Data collection methods include questionnaires distributed to 59 respondents, observations, interviews, and document analysis. Data processing was conducted through statistical data analysis. The results indicate that the implementation of the ODOA method in the eighth grade at Mts Al-Musadaddiyah Garut achieved an average score of 84.7%, indicating a "Very Good" rating. Similarly, the success in memorizing Juz 30 of the Qur'an among eighth-grade students at Mts Al-Musadaddiyah Garut received an average score of 87.5%, also categorized as "Very Good." Statistical analysis reveals that the ODOA method accounts for 54.86% of the success in memorizing Juz 30 among the students, while other factors influencing Qur'anic memorization, accounting for 45.14%, were not investigated in this study. These findings highlight the positive impact of the ODOA method on the success of Qur'anic memorization. Keywords: One Day One Ayah Method, Success in Memorizing Juz 30 of the Qur'an`